COVID-19 global pandemic planning: Dry heat incubation and ambient temperature fail to consistently inactivate SARS-CoV-2 on N95 respirators - Perkins, Douglas J (Exp Biol Med (Maywood), 2020)
The ongoing pandemic of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has placed a substantial strain on the supply of personal protective equipment, particularly the availability of N95 respirators for frontline healthcare personnel. These shortages have led to the creation of protocols to disinfect and reuse potentially contaminated personal protective equipment. A simple and inexpensive decontamination procedure that does not rely on the use of consumable supplies is dry heat incubation. Although reprocessing with this method has been shown to maintain the integrity of N95 respirators after multiple decontamination procedures, information on the ability of dry heat incubation to inactivate SARS-CoV-2 is largely unreported. Here, we show that dry heat incubation does not consistently inactivate SARS-CoV-2-contaminated N95 respirators, and that variation in experimental conditions can dramatically affect viability of the virus. Furthermore, we show that SARS-CoV-2 can survive on N95 respirators that remain at room temperature for at least five days. Collectively, our findings demonstrate that dry heat incubation procedures and ambient temperature for five days are not viable methods for inactivating SARS-CoV-2 on N95 respirators for potential reuse. We recommend that decontamination procedures being considered for the reuse of N95 respirators be validated at each individual site and that validation of the process must be thoroughly conducted using a defined protocol.